Возбуждение гигантского дипольного резонанса излучением (110) каналированных электронов в кристалле Si - Ашурко, Никита Андреевич (Перспективы развития фундаментальных наук. Т. 1 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25-28 апреля 2023 г.)
As part of this research work, we have proposed the model for the excitation of a giant dipole resonance based on radiation channeling, considered numerical structure of gold, lead, and uranium, and constructed outputs for giant dipole resonances.